Using VR Technologies in Professional Education - Qambarov Bahriddin Panji o‘g‘li (Academia One Publishing, 2024)
this article highlights the theory and possibilities of using VR technologies in professional education.
Keywords: information technology; VR; online lesson; immersive dasr